Digitalization, Strategic Orientations and SME Internationalization: A fs/QCA Study - Anna KWIOTKOWSKA (Communications of International Proceedings, 2021)
The ability to internationalize has become a competitive necessity for many companies, important to their survival and development in the globalization era. Simultaneously smart and digitalized technologies (Internet of Things and Services, Big data etc.) enable SMEs to overcome the barriers of geographical location, while giving access to international markets. Digitalization is transforming the locus of entrepreneurial opportunities and entrepreneurial practices, thus offering new perspectives on internationalization. As prior studies recognize internationalization requires strategic orientations such as entrepreneurial orientation, market orientation and learning orientation, but the discussion rarely includes digitalization. The aim of this research is to find causal patterns that explain the SMEs' internationalization behavior. This study uses a fuzzy-set qualitative comparative analysis (fs/QCA) to analyze how digitalization and strategic orientations relate to SMEs' internationalization behavior. The sample consists of 158 manufacturing small and medium enterprises (SMEs) located in Poland. The results suggest that different combinations of digitalization and strategic orientations attributes lead to internationalization effect (three configurations), international networking activities (two configurations), and international know-how activities (two configurations). The use of fs/QCA to explore how alternative combinations of digitalization and strategic orientations lead to internationalization behavior constitutes an important contribution to the literature.
Keywords: SME internationalization; digitalization; entrepreneurial orientation; market orientation; learning orientation; fs/QCA.